A novel separator coated by carbon for achieving exceptional high performance lithium-sulfur batteries. (February 2016) - Zhu, Jiadeng; Ge, Yeqian; Kim, David; Lu, Yao; Chen, Chen; Jiang, Mengjin; Zhang, Xiangwu
Abstract: Lithium-sulfur batteries have received intense attention because of their high theoretical capacity, low cost and environmental friendliness. However, low active material utilization and poor cycle life limit their practical applications. Here, we report a strategy to obtain high capacity with long cycle life and rapid charge rate by introducing a carbon coating on the separator. Excellent cycling performance with a high capacity 956 mAh g −1 after 200 cycles and outstanding high-rate response up to 4 C are achieved, which are among the best reports so far. High electrochemical performance can be obtained even at a high sulfur loading of 3.37 mg cm −2 . Such improved results could be ascribed to the conductive carbon coating, which not only reduces the cell resistance but blocks the diffusion of soluble polysulfides avoiding shuttle effect during cycling. This study demonstrates a feasible, low cost and scalable approach to address the long-term cycling challenge for lithium-sulfur batteries. Graphical abstract: Highlights: GF has been demonstrated as a novel separator for Li-S batteries. Li-S cells with CGF have shown excellent cycling stability and rate capability. The CGF separator significantly inhibits the migration of polysulfide intermediates.